Association of Plasminogen Activator Inhibitor 1 (PAI-1) 4G/5G Polymorphism and Susceptibility to SLE in Egyptian Children and Adolescents: A Multicenter Study - Yousef AA; Mohamed FY; Boraey NF; Akeel NE; Soliman AA; Waked NM; Hashem MIA; Shehata H; Fahmy DS; Ismael A; Ibrahim LM; Ibrahim MAM; et al. (Journal of Inflammation Research, 2020)
Aly A Yousef,1 Faisal Y Mohamed,2 Naglaa F Boraey,3 Nagwa E Akeel,4 Attia A Soliman,4 Nevin M Waked,5 Mustafa IA Hashem,4 Hassan Shehata,4 Dalia S Fahmy,6 Ali Ismael,7 Lamya M Ibrahim,8 Mohamed AM Ibrahim,9 Hanan F Salem,10 Sherif M Yousry,11 Sherif F Osman,12 Rania A Fouad,13,14 Eman T Enan,15,16 Mohammed A Attia,17,18 Mona R Afify,19 Nancy MS Zeidan,20 Mohamed Nashat21 1Department of Pediatrics, Faculty of Medicine, Helwan University, Helwan, Egypt; 2Department of Pediatrics, Faculty of Medicine, Ain-Shams University, Cairo, Egypt; 3Department of Pediatrics, Faculty of Medicine, Sohag University, Sohag, Egypt; 4Department of Pediatrics, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 5Department of Pediatrics, Faculty of Medicine, October 6 University, October 6, Egypt; 6Department of Rheumatology, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 7Department of Internal Medicine, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 8Department of Clinical Pathology, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 9Department of Clinical Pathology, Faculty of Medicine, Sohag University, Sohag, Egypt; 10Department of Anesthesia, Faculty of Medicine, Banha University, Banha, Egypt; 11Department of Clinical Pathology, Faculty of Medicine, Cairo University, Cairo, Egypt; 12Department of Radiology, Texas Tech University Health Sciences Center, El Paso, TX, USA; 13Department of Medical Biochemistry, College of Medicine, El-Mareefa University, Riyadh, Kingdom of Saudi Arabia; 14Department of Medical Biochemistry, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 15Department of Pathology, College of Medicine, El-Mareefa University, Riyadh, Kingdom of Saudi Arabia; 16Department of Pathology, Faculty of Medicine, Mansoura University, Mansoura, 35516, Egypt; 17Department of Clinical Pharmacology, College of Medicine, El-Mareefa University, Riyadh, Kingdom of Saudi Arabia; 18Department of Clinical Pharmacology, Faculty of Medicine, Mansoura University, Mansoura, 35516, Egypt; 19Department of Medical microbiology and Parasitology, Faculty of Medicine, University of Jeddah, Jeddah, 21589, Saudia Arabia; 20Department of Pediatrics, Faculty of Medicine, Cairo University, Cairo, Egypt; 21Department of Pediatrics, Faculty of Medicine, Aswan University, Aswan, EgyptCorrespondence: Faisal Y MohamedFaculty of Medicine, Ain-Shams University, Cairo, EgyptTel +201113363638Email Faisalyousef69@gmail.comBackground: Plasminogen activator inhibitor-1 (PAI-1) is a key molecule residing at the nexus between thrombosis and inflammatory processes. Recently, PAI-1 and its gene expression have emerged as a potential candidate for autoimmune disorders such as SLE.Objective: To investigate whether the PAI-1 4G/5G polymorphism at position − 675 could be a genetic marker for susceptibility to childhood-onset SLE and development of lupus nephritis among Egyptian children and adolescents.Methods: Three hundred fifty patients diagnosed with childhood-onset SLE and 350 well-matched healthy controls were included in this multi-center study. All subjects were genotyped for the PAI-1 promoter 4G/5G polymorphism at position − 675 using PCR– restriction fragment length polymorphism (RFLP). Serum PAI-1 levels were measured by ELISA.Results: The PAI-1 (- 675) 4G/4G genotype was more represented in c-SLE patients, as compared to the control group (38% vs 23%; OR =2.7; [95% CI: 1.47– 2.9]; P < 0.001). Patients carrying the PAI-1 4G/4G genotype or 4G allele were more likely to develop lupus nephritis (OR: 3.38; [95% CI: 1.9– 5.9]; P < 0.001, for the 4G/4G genotype and OR: 2.6; [95% CI: 1.85– 3.67]; for the 4G allele; P < 0.01). The PAI-1 4G/4G genotype was associated with higher PAI-1 serum concentrations (mean; 86.6± 22.7 ng/mL) as compared to those with a 4G/5G genotype (mean; 48.3± 16.5 ng/mL) and the lowest for the 5G/5G genotype (mean; 34.7± 11.4 ng/mL); P = 0.004.Conclusion: The PAI-1 4G/5G polymorphism may confer susceptibility to childhood-onset SLE and development of lupus nephritis among Egyptian children and adolescents. Moreover, the PAI-1 4G/4G genotype and 4G allele were associated with higher PAI-1 serum levels and higher disease activity scores.Keywords: plasminogen activator inhibitor-1, PAI-1, gene polymorphism, SLE, children, adolescents